Effect of Environmental Enrichment on the Body Weight in Broiler Chickens - Jacob, F. G.; Salgado, D. A. [UNESP]; Naa, I. A.; Baracho, M. S. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2020)
The present study had the objective of analysing the impact of the use of environmental enrichment (music and light stimuli), broiler sex, and age in broiler chickens' weight during growth. The observational study was carried out on a commercial farm. The environmental enrichment consisted of broilers' stimulation by sound and light, and a house was kept without stimulus (control). The music stimuli consisted of different music styles and was played during the experiment to promote motivation for the birds. The light stimuli came from a coloured (red and green) LED strobe projector. Both stimuli were applied once a day for about 6 minutes, for five weeks. The broilers were weighed at the end of each week of growth. Throughout the growth period, broiler behaviours were analysed weekly through videos, and the leg disorders of the birds were put into score evaluations. The effects of the environmental enrichment type, gender, and age, and the probable interactions of these variables, on the weight of the broiler chickens were analysed by the comparative analysis of means, analysis of variance (ANOVA), and Tukey test of multiple comparisons. 7, 14, and 21 day old broiler chickens did not differ on body weight when compared with age, gender, and environmental enrichment (broiler house) (p>0.05). Males from 21 days of age had an increase in body weight when compared with females. Light enrichment presented the lowest body weight when compared with all studied houses, while the absence of enrichment presented the highest broiler weight.
Keywords: Broiler production; broiler welfare; music; light